A note on the effect of temperature on the friction and wear behaviour of carbon-fibre-reinforced Polyetheretherketone (PEEK-CF30) at dry sliding. (22nd November 2005) - Davim, J. Paulo; Cardoso, Rosaria
In this study, an evaluation was made of the composite PEEK-CF30 tribological (friction and wear) behaviour at selected temperatures in a range of 60–180°C and at pv = 0.5, 1.5 and 3.0 MPa m/s. The friction and wear tests were performed on a pin-on-disc machine. As testing temperature increased from below to above the glass transition temperature (Tg ) of the polymer matrix, wear and friction transitions occurred. An increase in testing temperature resulted in higher specific wear rates and, in general, in lower friction coefficient.